Voices of formerly Enslaved Corpus - Elmerot, Irene; Olsson, Leif-Jöran; Rönnbäck, Klas (University of Gothenburg, 2025)
The Voices of formerly Enslaved Corpus (Pilot)

A corpus of transcribed and annotated narratives from informants who were formerly enslaved. Texts selected are mainly in vernacular English, but partly also in standard English [eng]. There are two main parts:

Selection of narratives collected in the Federal Writers' Projct (FWP) collected in late 1930's and published in 1941.
Selection of narratives collected as part of the Documenting the American South Collection (DocSouth)

The Corpus has been developed in collaboration with Språkbanken Text.

For more on annotation, preparation of data, and acknowledgements see:

IE, LJO, KR. (202x). Voices of the formerly Enslaved Corpus, Pilot v0.1. [forthcoming][Where], pp nn--nn.

For questions about the corpus:
Klas Rönnbäck klas.ronnback@econhist.gu.se

If you notice any errors or inconsistencies in annotations, please report them to this email address.

Main contributors:

Irene Elmerot
Researcher, University of Gothenburg
Leif-Jöran Olsson
Senior Research Engineer, University of Gothenburg
Klas Rönnbäck
PI and Senior Researcher, University of Gothenburg

The Voices of formerly Enslaved Corpus (Pilot)

A corpus of transcribed and annotated narratives from informants who were formerly enslaved. Texts selected are mainly in vernacular English, but partly also in standard English [eng]. There are two main parts:

Selection of narratives collected in the Federal Writers' Projct (FWP) collected in late 1930's and published in 1941.
Selection of narratives collected as part of the Documenting the American South Collection (DocSouth)

The Corpus has been developed in collaboration with Språkbanken Text.

For more on annotation, preparation of data, and acknowledgements see:

IE, LJO, KR. (202x). Voices of the formerly Enslaved Corpus, Pilot v0.1. [forthcoming][Where], pp nn--nn.

For questions about the corpus:
Klas Rönnbäck klas.ronnback@econhist.gu.se

If you notice any errors or inconsistencies in annotations, please report them to this email address.

Main contributors:

Irene Elmerot
Researcher, University of Gothenburg
Leif-Jöran Olsson
Senior Research Engineer, University of Gothenburg
Klas Rönnbäck
PI and Senior Researcher, University of Gothenburg
votfe-pilot
Keywords: Language Technology (Computational Linguistics); economical history; slavery; abolitionism; discourse analysis; occupations; power relations; first person narratives; corpus; Natural Language Processing; Språkbehandling och datorlingvistik